(3Gdbhd GdJGe aj aVd GdQei HGdSgGes - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGei GdYOh HGdSge GdYQHi GdCTQa , hMGei eJHYi GdHGWd Yf GdYdh HGdhge hGdMSGe GdeQga hHYO adeG cGf GdQei HGdSgGe ef CLd CfhGY GdaQhSjI aCLHJ Cf CJMage ai aVdg HcJGH HOjY UfabI ajg s
(3BNQgG (B:s
(3bGd agPG UdGM GdYHGO hGdHdGO bGd abjd GHf GdeHQc LHgI GdaVjd QVgeG Gddg hbGd jG eYde GdNjQ ef jMSf gPG ZjQc BNQ Gdbhd GdJGe hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3cJHJ ai ejGI GdeDdas
(3hbO aQZ GdeDda ef JCdjag SfI (B875 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1363s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs